2011
DOI: 10.1007/s10562-011-0682-3
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acidic Ionic Liquids Mediated Metallic Salts Catalytic System for the Chemical Fixation of Carbon Dioxide to Form Cyclic Carbonates

Abstract: The catalysts of COOH-and SO 3 H-functionalized ionic liquids mediated metallic salts had been developed for the coupling of carbon dioxide and epoxides to form cyclic carbonates under mild reaction conditions without using additional organic solvents. The effects of different ionic liquids, metallic salts, varying the molar ratio of ionic liquid to metallic salt and reaction conditions were examined. The excellent yield of cyclic carbonates and the high turnover frequencies (TOF) were obtained at the optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
(65 reference statements)
2
28
0
Order By: Relevance
“…In comparison, almost no product was detected when ZnO or Zn(NO3)2 was used (Entries 7 and 8) and the reaction hardly occurred or very low conversions were obtained over GndCl with Cd (Entries 9-12). The catalytic activity improved with the stronger anionic nucleophilic property of zinc halide in the order of ZnI2 >>ZnBr2 >ZnCl2, which was in accordance with previous works [8,23]. When ZnBr2 and ZnCl2 were used as the co-catalysts, 43% and 12% yield of PC were obtained, respectively (Entries 5 and 6), and ZnI2 co-catalyst displayed a remarkable role in accelerating the reaction with 94% PC yield.…”
Section: Screening Of Catalysts and Their Reusabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…In comparison, almost no product was detected when ZnO or Zn(NO3)2 was used (Entries 7 and 8) and the reaction hardly occurred or very low conversions were obtained over GndCl with Cd (Entries 9-12). The catalytic activity improved with the stronger anionic nucleophilic property of zinc halide in the order of ZnI2 >>ZnBr2 >ZnCl2, which was in accordance with previous works [8,23]. When ZnBr2 and ZnCl2 were used as the co-catalysts, 43% and 12% yield of PC were obtained, respectively (Entries 5 and 6), and ZnI2 co-catalyst displayed a remarkable role in accelerating the reaction with 94% PC yield.…”
Section: Screening Of Catalysts and Their Reusabilitysupporting
confidence: 89%
“…The desired product yield was obtained even at low CO2 pressure of 1.0 MPa over GndCl/ZnI2 catalysts. A similar effect of CO2 pressure on catalytic activity was observed in other catalytic systems [6,[25][26][27], which could be explained by the fact that the introduced CO2 was dissolved in propylene oxide or "liquefied" by the formation of a CO2-PO complex [23]. In the low-pressure range, increasing CO2 pressure led to an increase of CO2-PO concentration in the liquid phase and thus enhanced the PC yield.…”
Section: Effect Of Reaction Parameterssupporting
confidence: 68%
“…The IL precursors, as well as compound 4c that was used as a reference substance, were synthesized in close analogy to the recent literature. 27,28 Details can be found in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Other types of catalysts used in the synthesis of cyclic carbonates are ionic liquids with halide anions and cations functionalized with Brønsted acidic groups such as ‐COOH and ‐SO 3 H . The role of the functional group is to coordinate the oxygen atom of epoxide, which leads to polarization of the C–O bond in the epoxide ring.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic liquids described above carry an acidic functionality in the cation. To the best of our knowledge, only Xiao et al reported the use of ionic liquid which in addition to the cation with the acidic group, has the acidic anion HSO 4 − . However, 1‐methyl‐3‐(4‐sulfobutyl)imidazolium hydrogensulphate was inactive in the synthesis of propylene carbonate.…”
Section: Introductionmentioning
confidence: 99%